The Effectiveness of Guided Inquiry with Mind Mapping to Improve Science Process Skills and Learning Motivation - Prastiwi, Dewi; Sri Haryani, Sri Haryani; Lisdiana, Lisdiana (Journal of Primary Education, 2018)
Science learning based on the 2013 curriculum is implemented in scientific inquiry to develop scientific work. The purpose of this research is to analyze the effectiveness of guided inquiry model with mind mapping to improve science process skill and student learning motivation. The research is used quasi experimental model with nonequivalent control group design. Data collection methods used in this research include test methods, observation, interviews and documentation. The data were analyzed by using quantitative descriptive analysis. The results showed that the use of guided inquiry model with mind mapping effective to improve science process skill and motivation of fourth grade student of SDN Krobokan. There is a significant difference of science skill score between experimental and control class with significance level of 5%. The acquisition of experimental class obtain N-Gain value of 0.47 in medium category and control class 0.27 in low category. The guided inquiry model with mind mapping is also effective in student learning motivation. This is evidenced by the score of motivation to learn in the experimental class that is 76 on the satisfied category and control class of 72 in good category. The results of correlation test shows a very strong relationship between the science process skills with student learning motivation. It shown from the correlation value of 0.938 with 1% significance level and the direction of positive relationships,. It can be conclude that the higher the score of students' science process skills the higher the student learning motivation.